2013
DOI: 10.1002/chem.201204633
|View full text |Cite
|
Sign up to set email alerts
|

Selective Ruthenium‐Catalyzed Transfer Hydrogenations of Nitriles to Amines with 2‐Butanol

Abstract: Transfer your hydrogen: Fast and general transfer hydrogenation of nitriles to form primary amines is possible with a homogeneous Ru/1,4-bis(diphenylphosphino)butane (DPPB) catalyst (see scheme). The use of 2-butanol as the hydrogen-transfer reagent is essential for the selective reduction of aromatic, heteroaromatic, and aliphatic nitriles with this system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 82 publications
(67 reference statements)
1
33
0
Order By: Relevance
“…It is well known that platinum clusters are capable of dissociating activation of H 2 molecules (Figure , II) . The dissociated H atoms then diffuse over the MOF surface by spillover to reach the adsorbed nitrile molecule, hydrogenating the CN bond to form a primary imine intermediate (Figure , III), which is very active and can be further hydrogenated to produce a primary amine . The Lewis base (DABCO) site could obtain a proton from amine to form the intermediate V .…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that platinum clusters are capable of dissociating activation of H 2 molecules (Figure , II) . The dissociated H atoms then diffuse over the MOF surface by spillover to reach the adsorbed nitrile molecule, hydrogenating the CN bond to form a primary imine intermediate (Figure , III), which is very active and can be further hydrogenated to produce a primary amine . The Lewis base (DABCO) site could obtain a proton from amine to form the intermediate V .…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, 2 was inactive in this reaction even at elevated temperatures (70 °C), whereas 3 and 4 showed comparable activity only upon heating to 70 °C. Our research was in progress when Beller and co‐workers reported the first general protocols for the Ru‐catalysed TH of nitriles to primary amines13 and to alkylated secondary amines,14 in which the latter products stem from a domino sequence of reduction, coupling with ketone and hydrogenation. However, both processes require a high temperature (120 °C).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, nitriles are not typical substrates for TH and are actually often used as solvents for these reactions. Only a few and generally low‐yielding examples of nitrile TH to primary amines are known,4, 10, 12 with the notable exception of the report of Beller and co‐workers on the [Ru( p ‐cymene)Cl 2 ] 2 /1,4‐bis(diphenylphosphino)butane (DPPB) system that catalyses the reduction of aromatic and aliphatic nitriles by 2‐butanol at 120 °C 13. Beller and co‐workers also found that if the catalyst is changed to RuCl 2 (PPh 3 ) 3 the synthesis of secondary amines is allowed because of a concomitant reductive amination of acetone, derived from isopropanol, with the primary amine formed at the TH stage 14.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies on heterogeneous catalysts, such as Ni/Raney and Pd/C, for reduction of nitriles led to low selectivity and various amines by‐products. Homogenous transfer hydrogenation of nitriles is relatively underdeveloped, with only a handful of examples;, and these previous studies involved mostly high catalyst loadings, required high temperatures, and/or utilised wasteful reducing reagents . Transfer hydrogenation of nitriles leads to three types of products: primary amines, imines formed as a result of coupling of amine with the carbonyl by‐product derived from alcohol, and secondary amines formed as a result of transfer hydrogenation of imine intermediates.…”
Section: Introductionmentioning
confidence: 99%
“…Transfer hydrogenation of nitriles leads to three types of products: primary amines, imines formed as a result of coupling of amine with the carbonyl by‐product derived from alcohol, and secondary amines formed as a result of transfer hydrogenation of imine intermediates. High temperatures usually favour the latter type of products ,. These complications can be avoided, in principle, by using formates as the hydrogen source.…”
Section: Introductionmentioning
confidence: 99%